Impacts of Justice Collaborator Revocation from Prisoner Remissions for Extraordinary Crimes in Class 1 Correctional Facilities in Tangerang - Amiludin, Amiludin; Dias Saputra, Muhamad; Bukhari Razif, Imran; Nurfauziah Ahmad, Dwi (Indonesia Law Reform Journal, 2023)
The elimination of Justice Collaborator as a requirement for an Extraordinary Crime convict to obtain sentence reduction or remission, in accordance with the provisions stated in the Minister of Law and Human Rights Regulation Number 7 of 2022, which amends the Minister of Law and Human Rights Regulation Number 3 of 2018 regarding the requirements and procedures for granting sentence reduction, has changed the mechanism for granting remission to prisoners at Class 1 Tangerang Correctional Institution, both in terms of administrative and subjective requirements. This change has both positive and negative impacts on the existing regulations. The research methodology employed is empirical legal research, as it relates to the effectiveness of the law. The recommendations obtained are related to communication, education, and transparency regarding the implementation of Minister of Law and Human Rights Regulation Number 7 of 2022 at Class 1 Tangerang Correctional Institution, in order to be accepted and understood by the inmates, their families, and relevant stakeholders